The Cognate and False Cognate Knowledge of Young Emergent Bilinguals. Issue 2 (7th January 2016) - Simpson Baird, Ashley; Palacios, Natalia; Kibler, Amanda
Abstract : This study examined young emergent bilinguals' cognate and false cognate knowledge and vocabulary outcomes on four early‐language assessments in English and Spanish. Findings revealed that children were able to use shared phonology of words—before they had developed extensive knowledge about their orthography—to recognize and produce cognates. In addition, children were not confused by the similar phonology in semantically different words when recognizing and producing false cognates. This indicates that children who are just beginning to acquire literacy may also possess a "bilingual advantage" when identifying cognate items as do their older peers.